Ex Vivo Irradiation of Lung Cancer Stem Cells Identifies the Lowest Therapeutic Dose Needed for Tumor Growth Arrest and Mass Reduction In Vivo - Puglisi, Caterina; Giuffrida, Raffaella; Borzì, Giuseppina; Illari, Salvatore; Caronia, Francesco Paolo; Di Mattia, Paolo; Colarossi, Cristina; Ferini, Gianluca; Martorana, Emanuele; Sette, Giovanni; Eramo, Adriana; Lorico, Aurelio; et al. (Frontiers in Oncology, 2022)
Radiotherapy represents a first-line treatment for many inoperable lung tumors. New technologies offer novel opportunities for the treatment of lung cancer with the administration of higher doses of radiation in smaller volumes. Since both therapeutic and toxic treatment effects are dose-dependent, it is important to identify a minimal-dose protocol for each individual patient that maintains efficacy while decreasing toxicity. Cancer stem cells sustain tumor growth, promote metastatic dissemination and may give rise to secondary resistance. The identification of effective protocols targeting these cells may improve disease-free survival of treated patients. In this work, we evaluated the existence of individual profiles of sensitivity to radiotherapy in patient-derived CSCs using both in vitro and in vivo models. Both CSCs in vitro and mice implanted with CSCs were treated with radiotherapy at different dose intensities and rates. CSCs response to different radiation doses greatly varied among patients. In vitro radiation sensitivity of CSCs corresponded to the therapeutic outcome in the corresponding mouse tumor model. On the other side, the dose administration rate did not affect the response. These findings suggest that in vitro evaluation of CSCs may potentially predict patients’ response, thus guiding clinical decision.